THE CONSTITUTIONALITY OF INTERNATIONAL INVESTMENT AGREEMENTS IN INDONESIA POST ISSUANCE OF THE CONSITUTIONAL COURT DECISION NUMBER 13/PUU-XVI/2018 - Jessica Marpaung (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2020)
As a developing country participating in international economy, Indonesia has declared a clear commitment to create a stable and conducive environment for investment. Such endeavor has been met fraught with challenges, especially from within the country itself. Challenges to the constitutionality of Investment International Agreements (IIAs), including both Free Trade Agreements (FTAs) and Bilateral Investment Treaties (BITs) forged between Indonesia and various countries have arisen and recently led to a constitutional claim, resulting in the Decision No. 13/PUU-XVI/2018 (Decision No. 13/2018). Allegations that the discriminatory and unfair treatment against local businessmen caused by such IIAs clearly constitutes a violation of the Constitution, rendering IIAs that have been signed to-date reviewable, and more extremely, unconstitutional, and must be terminated. This Article aims to discuss on assess the issue of constitutionality of IIAs, especially through the discussions in Decision No. 13/2018, and its impact on Indonesia’s commitment to IIAs.